Time variations of H2O and SiO masers in the proto-Planetary Nebula OH 231.8+4.2. Issue 1 (4th July 2019) - Kim, Jaeheon; Cho, S-H; Bujarrabal, V; Imai, H; Dodson, R; Yoon, D-H; Zhang, B
ABSTRACT: H2 O (22 GHz) and SiO masers (43, 86, 129 GHz) in the bipolar proto-planetary nebula OH 231.8+4.2 were simultaneously monitored using the 21-m antennas of the Korean VLBI Network in 2009–2015. Both species exhibit periodic flux variations that correlate with the central star's optical light curve, with a phase delay of up to 0.15 for the maser flux variations with respect to the optical light curve. The flux densities of SiO v = 2, J = 1→0 and H2 O masers decrease with time, implying that they may disappear in 10–20 yr. However, there seems to have been a transient episode of intense H2 O maser emission around 2010. We also found a systematic behaviour in the velocity profiles of these masers. The velocities of the H2 O maser components appear to be remarkably constant, suggesting ballistic motion for the bipolar outflow in this nebula. On the other hand, those of the SiO maser clumps show a systematic radial acceleration of the individual clumps, converging to the outflow velocity of the H2 O maser clumps. Measuring the full widths at zero power of the detected lines, we estimated the expansion velocities of the compact bipolar outflow traced by H2 O maser and SiO thermal line, and discussed the possibility of the expanding SiO maser region in the equatorial direction. All of our analyses support that the central host star of OH231.8 is close to the tip of the AGB phase and that the mass-loss rate recently started to decrease because of incipient post-AGB evolution.